Approaches and Differences on the Ratio Between History and Sociology - Sota, Jani (Richtmann Publishing, 2012)
Today’s society constantly raises issues related to our lives, both in personal and social plans. Handling and resolving theseissues often require not only scientific knowledge but skills and attitudes to engage in discussions related to Historycal events andespecially to make critical judgments in dealing with sociological issues. Determining the difference between History and Sociology helpspeople understand the impact of socio-economic activities and people in the community where we live, highlights developments inrelations between local, national and global level; highlights the ability of citizens to influence the life of community and beyond;examines breadth and depth of sustainable development issues and promotes respect for people and other cultures in the environmentwhere we live.